The Pedicled Buccal Fat Pad: Anatomical Study of the New Flap for Skull Base Defect Reconstruction After Endoscopic Endonasal Transpterygoid Surgery - Golbin, Denis A.; Lasunin, Nikolay V.; Cherekaev, Vasily A.; Polev, Georgiy A. (Journal of Neurological Surgery Part B: Skull Base, 2017)
Objectives To evaluate the efficacy and safety of using a buccal fat pad for endoscopic skull base defect reconstruction.Design Descriptive anatomical study with an illustrative case presentation.Setting Anatomical study was performed on 12 fresh human cadaver specimens with injected arteries (24 sides). Internal carotid artery was exposed in the coronal plane via the endoscopic transpterygoid approach. The pedicled buccal fat pad was used for reconstruction.Participants: 12 human cadaver head specimens; one patient operated using the proposed technique.Main outcome measures: Proximity of the buccal fat pad flap to the defect, compliance of the flap, comfort and safety of harvesting procedure, and compatibility with the Hadad–Bassagasteguy nasoseptal flap.Results: Harvesting procedure was performed using anterior transmaxillary corridor. The pedicled buccal fat pad flap can be used to pack the sphenoid sinus or cover the internal carotid artery from cavernous to upper parapharyngeal segment.Conclusion The buccal fat pad can be safely harvested through the same approach without external incisions and is compliant enough to conform to the skull base defect. The proposed pedicled flap can replace free abdominal fat in central skull base reconstruction. The volume of the buccal fat pad allows obliteration of the sphenoid sinus or upper parapharyngeal space.
Keywords: buccal fat pad; endoscopic endonasal approach; transpterygoid approach; skull base defect; skull base reconstruction